Predictors of sperm retrieval with micro TESE, A narrative review article - Abedi, Amir Reza; Montazeri, Saeed; Ghiasy, Saleh; Aliakbari, Ferershte (Archives of Men's Health, 2020)
Introduction: Regarding the financial and psychological effects of micro-TESE on patients with NOA, it is important to determine the parameters by which the sperm retrieval with micro-TESE can be predicted. Methods: The key words used for conducting a search in the PubMed database included nonobstructive azoospermia and TESE. The abstracts of the articles were reviewed, and the articles which reported the parameters’ influence on sperm retrieval with micro TESE were included. All non-English papers, case reports, and case series, were excluded from the review. Eventually, 25 articles were selected to be included. Results: It is recommended that diagnostic test is biopsy should be performed at the time of micro-TESE. The histopathology of testis, testicular volume, hormone profile, aging, and genetic factors, are parameters that might influence the results of sperm retrieval with micro-TESE. Heterogeneous histopathological pattern and report of hypospermatogenesis on pathology, lower serum FSH level, normal testis volume, and varicocelectomy, increase the chance of sperm retrieval with micro-TESE. In terms of sperm retrieval, some genetic factors such as AZFa, AZFb, and chromosome Y micro deletion provide poor prognosis. Conclusion: Testis histopathology is the most important factor which predicts sperm retrieval with micro-TESE. Other factors that influence the sperm retrieval rate are testis volume, genetic factor, serum FSH level, and history of varicocelectomy.